Preliminary findings and research perspectives on the German modal sollen in L2 written assessments - Wulff, Nadja; McGury, Sandra (Glottodidactica, 2024)
Modal verbs represent a special verb category and constitute an essential component of L2 German semantics. While Abrams and Rott (2017) suggest that German learner texts depict a 90% accuracy in the correct use of modal verbs in integrative writing tasks, the correct semantic use of the modal sollen (‘supposed to’; ‘should’) seems to pose a particular challenge (Jentges 2016), especially in an assessment context. In this corpus analysis, 1,032 L2 German assessment texts across all CEFR levels were analyzed with respect to the L2 semantic use of sollen against the backdrop of the assessment prompts. 68% of instances of all uses of sollen in A1 texts and 53% of all uses of sollen in A2 texts showed an inappropriate semantic use of sollen. The discrepancy between these results and Abrams and Rott (2017) can be attributed to the prompts used in the assessments analyzed in this paper: They do not take into consideration the semantic mismatch between the use of the modal in the prompt and its inappropriate use in the texts produced.